Climate change enables invasion of the portunid crab Charybdis bimaculata into the southern Bohai Sea - Zhang, Xiaomin; Shi, Yongchuang; Li, Shaowen; Yang, Yanyan; Xu, Bingqing; Wang, Xiuxia; Su, Haixia; Li, Fan (Frontiers in Marine Science, 2024)
In May 2020, a bottom-trawl survey in the southern Bohai Sea collected the portunid crab Charybdis bimaculata, a species formerly found in the northern Yellow Sea. In subsequent surveys, C. bimaculata was found to be abundant and likely to occupy habitats and niches of native species. To study the suitability of habitat in the southern Bohai Sea for this crab, nine trawl surveys were conducted between 2020 and 2022 to monitor its dispersal. Using Biomod2 software and combining species occurrence and environmental data, a distribution model for C. bimaculata in the southern Bohai Sea is developed. We analyze relationships between this and other crustacean species by comparing niche widths and their overlap. A random forest model outperforms eight others, and has the highest evaluation indices among single algorithm species-distribution models. The evaluation index of an ensemble model is significantly higher than those of single algorithm models, indicating its greater accuracy and robustness. We report suitable habitat for C. bimaculata to occur mainly in central and northeastern Laizhou Bay, and for this habitat suitability to shift over years from the middle to northeastern waters. Niche width showed a negative trend from 2020 to 2022, and is greater in May than August for each year. Niche overlaps between C. bimaculata and other major crustaceans in the southern Bohai Sea exist. We consider that increased sea surface temperature caused by climate change enabled invasion of C. bimaculata from northern Yellow Sea waters into the southern Bohai Sea, where it can overwinter and complete its life cycle. These results provide a scientific basis upon which monitoring of C. bimaculata in the Bohai Sea can be strengthened to better cope with its invasion and any negative impact on local biodiversity.